2002
DOI: 10.1007/s00464-001-9058-x
|View full text |Cite
|
Sign up to set email alerts
|

A new bipolar feedback-controlled sealing system for closure of the cystic duct and artery

Abstract: Cystic artery and cystic duct closure with the new device may be an alternative to the clip. Further trials should evaluate the feasibility and safety of the new device in the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 12 publications
1
27
0
Order By: Relevance
“…The increased IAP also triggers Neurohumoral responses of the vasopressin renin- The local effect of prolonged use of diathermy to the liver surface in laparoscopic cholecystectomy and the spread of heat to liver parenchyma may be another possibility [6] . This hypothesis is supported by some studies [12][13][14][15][16][17] . However, it remains to be explained why there is hepatic enzyme elevation in laparoscopic surgeries where the focus is far away from the liver.…”
Section: Discussionsupporting
confidence: 68%
“…The increased IAP also triggers Neurohumoral responses of the vasopressin renin- The local effect of prolonged use of diathermy to the liver surface in laparoscopic cholecystectomy and the spread of heat to liver parenchyma may be another possibility [6] . This hypothesis is supported by some studies [12][13][14][15][16][17] . However, it remains to be explained why there is hepatic enzyme elevation in laparoscopic surgeries where the focus is far away from the liver.…”
Section: Discussionsupporting
confidence: 68%
“…3,9,10) Vessels up to 7 mm in diameter can be safely divided and the successful sealing of animal vessels has been reported by several authors. The levels of burst pressures have been measured above the normal physiological range in abdominal 3) and pulmonary vessels.…”
Section: Discussionmentioning
confidence: 99%
“…16,17 It has been tried mainly in experimental animals for closer of cystic duct but human studies are lacking.4Its use in humans has been questioned by most of the authors and recommended need for further research. 10,18,19 The risk of lateral thermal injury in high-tech devices like harmonic and plasma kinetic may involve 0.5-2 mm of adjacent tissues. 20 Moreover excess traction on gallbladder and cystic duct during sealing process may burst tissues before sealing resulting in bile leak.…”
Section: Resultsmentioning
confidence: 99%
“…10 However, Shamiyeh and coworkers have also reported that use of harmonic scalpel and plasma kinetics may be contraindicated in cases of short cystic duct and acute cholecystitis due to high risk of complications. 4,19 Ligation of cystic duct and artery is safe and time-tested method in conventional open cholecystectomy. The art of intra corporeal ligation is a worth to imbibe for excelling in advanced laparoscopy.…”
Section: Resultsmentioning
confidence: 99%